Improving student learning outcomes in thematic learning of picture and picture type cooperative model through the tpack approach in elementary schools - Nasra, Nasra; Hamna, Hamna; Mustakim, Mustakim (Institute of Computer Science (IOCS), 2024)
This research is based on the background of the problem in students, namely the low learning outcomes of students in thematic learning in grade 5 SDN 3 Tolitoli. The low learning outcomes of students are influenced by the teacher aspect and the student aspect. This study aims to find out how the learning outcomes of students are by using a picture and picture type cooperative learning model with the TPACK approach. The method used is class action research (PTK) of the subjects in this study totaling 12 students. The object of research is SDN 3 Tolitoli, Baolan District, Tolitoli Regency. The data collection techniques used in this study are teacher observation, student observation and multiple-choice test. Before observation and tests are validated by expert validators and practitioners to ensure the feasibility and disfit of the research instruments used by researchers. The action was carried out in two cycles. The results of the study showed that there was an increase in thematic learning outcomes by using a picture and picture type cooperative model with a TPACK approach in grade V students of SDN 3 Tolitoli. Results The data analysis technique uses formulas to measure student presentations that show whether there is an increase in learning outcomes. The data obtained during the distribution of instruments in cycle I showed that only 5 students were active and in cycle 2 there were 10 students who were active in learning. Based on the results of the study, it can be concluded that the use of cooperative models with the TPACK and interactive Power Point approaches can both improve the ability of students' learning outcomes in thematic learning in grade 5